A New Index of Industrial Production and Trade - Persons, Warren M.; Foster, Le Baron R. (The Review of Economics and Statistics, 1933)
trade around the rising line of trend determined from the annual indexes. Crop production, Curve II, likewise advanced during the interval, but at a slower pace than industrial production and trade. Industrial and agricultural production combined, Curve III, follows the year-toyear fluctuations as well as the trend of industrial production and trade more closely than those of agricultural production. This is a result of the greater weight given to industry and trade than to agriculture because of the relatively greater importance of the former in our economic life. The percentage increases of the ordinates of the trend lines for I932, as compared with I899, for each of the three groups shown in Chart i are: (I) industrial production and trade, I 76 per cent; (II) crop production, 48 per cent; and (III) these combined, I32 per cent. The three years, I930-32, record a decline in physical production far exceeding that of any other period in the interval covered. Using the annual figures, the decline from I929 to I932 in the combined index is fully 4o per cent, as compared with a drop of less than I7 per cent from I920 to I92I, and ii per cent from I906 to I908. In other words, the most recent depression may be described as a major economic decline followed directly by another equally severe collapse. The, index of industrial production and trade, here presented, is constructed from series representing six major industrial groups: manufacture, wholesale and retail trade, railroad freight traffic, building construction, mining, and electric power production. Each of these series is presented in Chart 2 (next page), on a ratio scale in order to bring out rates of growth. Among the major groups, electric power production expanded most rapidly, while the volume of manufacture, wholesale and retail trade, railroad freight traffic, and mining grew more gradually. Building construction, on the other hand, exhibits no clearly defined trend, either upward or d wnward. We may rema k, however, that the index of building construction is based on estimates of the value of construction deflated by an index of building costs and the figures are less dependable, previous to I919, than those for any other series included in the present study. In fact, it is impossible to say, on the basis of available data for building construction, what the long time trend of construction actually was. The series is included, nevertheless, because reliable figures are available for I919 and after. Just as the industrial groups represented by the six constituents display divergent rates of growth of physical output, so their relative economic importance, measured in dollars, varies widely during the period covered by the index. 1 The index for total crops (agriculture) is that of Warren and Pearson, Prices, pp. 44-45. Although live stock is not included, feed crops as well as food and other crops are included, and the index measures agricultural production relative to the base period.